1995
DOI: 10.1093/clinids/21.5.1107
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Antecedent Antibiotic Use and Resistance to Extended-Spectrum Cephalosporins in Group I  -Lactamase-Producing Organisms

Abstract: Gram-negative pathogens are increasingly resistant to extended-spectrum cephalosporins (ESCs). Using a prospective, case-controlled observational study, we examined the prevalence and the risk factors for development of resistance to ESCs in group I beta-lactamase-producing organisms. Of the 386 isolates of Enterobacter species, Pseudomonas aeruginosa, Citrobacter species, and Serratia marsescens from 340 consecutive patients, 70 (18.1%) were resistant to ESCs; the highest rates of resistance were found among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
82
2
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(102 citation statements)
references
References 25 publications
9
82
2
3
Order By: Relevance
“…These bacteria can produce a cephalosporinase that is able to inactivate most of the cephalosporins. 2,3 The majority of these bacteria are inducible Enterobacteriaceae (Enterobacter spp, Serratia spp, Citrobacter spp, Morganella morganii, Providencia spp, Proteus vulgaris, Pantoea agglomerans). The relationship between the emergence of resistance of group I ␤-lactamase-producing organisms and the prior use of extended-spectrum cephalosporins is now clearly proven.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These bacteria can produce a cephalosporinase that is able to inactivate most of the cephalosporins. 2,3 The majority of these bacteria are inducible Enterobacteriaceae (Enterobacter spp, Serratia spp, Citrobacter spp, Morganella morganii, Providencia spp, Proteus vulgaris, Pantoea agglomerans). The relationship between the emergence of resistance of group I ␤-lactamase-producing organisms and the prior use of extended-spectrum cephalosporins is now clearly proven.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between the emergence of resistance of group I ␤-lactamase-producing organisms and the prior use of extended-spectrum cephalosporins is now clearly proven. 2 Another risk factor of developing resistance to extended-spectrum cephalosporins is the amount of previously used antibiotics. 2 The clinical consequence is that development of resistance may become particularly devastating in neutropenic patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data on preventing this type of resistance by employing concomitant aminoglycoside therapy is mixed. Jacobson et al (1995) found a lower incidence of emergence of resistance to extended-spectrum cephalosporins among patients treated with concomitant aminoglycoside therapy, while Chow et al (1991) did not.…”
Section: Beta-lactams and Extended Spectrum Cephalosporinsmentioning
confidence: 90%
“…26 Furthermore, micro-organisms detected in this study have been reported to cause nosocomial infection. 27,28 An antiseptic decontamination of the dental plaque with a 0.2% chlorhexidine gel decreased dental bacterial colonization and reduced the incidence of nosocomial infection in intensive care unit patients exposed to Operation duration (min)…”
Section: 10mentioning
confidence: 99%